Rhizospheric microbial communities are driven by Panax ginseng at different growth stages and biocontrol bacteria alleviates replanting mortality - Linlin Dong; Jiang Xu; Lianjuan Zhang; Ruiyang Cheng; Guangfei Wei; He Su; Juan Yang; Jun Qian; Ran Xu; Shilin Chen (Acta Pharmaceutica Sinica B, 2018)
The cultivation of Panax plants is hindered by replanting problems, which may be caused by plant-driven changes in the soil microbial community. Inoculation with microbial antagonists may efficiently alleviate replanting issues. Through high-throughput sequencing, this study revealed that bacterial diversity decreased, whereas fungal diversity increased, in the rhizosphere soils of adult ginseng plants at the root growth stage under different ages. Few microbial community, such as Luteolibacter, Cytophagaceae, Luteibacter, Sphingomonas, Sphingomonadaceae, and Zygomycota, were observed; the relative abundance of microorganisms, namely, Brevundimonas, Enterobacteriaceae, Pandoraea, Cantharellales, Dendryphion, Fusarium, and Chytridiomycota, increased in the soils of adult ginseng plants compared with those in the soils of 2-year-old seedlings. Bacillus subtilis 50-1, a microbial antagonist against the pathogenic Fusarium oxysporum, was isolated through a dual culture technique. These bacteria acted with a biocontrol efficacy of 67.8%. The ginseng death rate and Fusarium abundance decreased by 63.3% and 46.1%, respectively, after inoculation with B. subtilis 50-1. Data revealed that microecological degradation could result from ginseng-driven changes in rhizospheric microbial communities; these changes are associated with the different ages and developmental stages of ginseng plants. Biocontrol using microbial antagonists alleviated the replanting problem. KEY WORDS: Panax ginseng, Microbial communities, Replanting problem, High-throughput sequencing, Different ages, Bioremediation